Програмна система для автоматизації маркетингової діяльності шляхом аналізу поведінки людей - Гурова, Ю. В. (ХНУРЕ, 2020)
The main goal of this article is talk about one of the most important problem in marketing activities and discuss solutions of this problem. The work covers the main aspects of the problem and describes the main goal of any store owner to increase leads and demand for a product or service. Also, this work describes one of the many solutions that will help automate marketing activities by analyzing people's behavior. This solution based on one board computers and BLE (Bluetooth Low Energy) devices. The person's trajectory computes by bluetooth signal strength from all microcomputers to one BLE device. These BLE devices called Beacon. Beacon like lighthouse that send some data to devices, that are in BLE signal range.